'We're going around the subject' improving sex education and adolescents' awareness of sexually transmitted infections: a qualitative study. Issue 1 (2nd January 2021) - Seiler-Ramadas, Radhika; Mosor, Erika; Omara, Maisa; Grabovac, Igor; Schindler, Karin; Niederkrotenthaler, Thomas; Dorner, Thomas E.
ABSTRACT: Relatively few studies have identified the means to improve the quality of sex education in schools. This study aimed to qualitatively investigate whether sex education in Austria facilitates the development of adolescent sexuality and awareness of sexually transmitted infections (STIs) and highlights practical ideas that could help achieve a comprehensive form of sex education in schools. Semi-structured interviews were conducted with amaximum variation sample of thirteen male and female participants (aged 15–57 years). Transcriptions were coded and thematically analysed. A qualitative interpretative approach was used to refine codes and build categories to generate themes that defined sex education from participants' perspectives. Sex education was described as teaching the facts without addressing the emotions involved. Stigma and embarrassment were viewed as hinderingeffective communication, and STI awareness among adolescents was felt to be inadequate. Suggestions for improvement included using visual and tangible material, organising insightful excursions, and facilitating student presentations and group discussions. There currently exists a lack of effective sex education conveyingmeaningful information to improve adolescent sexuality and awareness of STIs. This study describes practical tools on how sex education can be creatively implemented to help young people develop critical reflective skills and strengthen their personal learning experiences.